Removal of Chromium (VI) and Lead (II) from aqueous solution by using bamboo waste as biosorbent / Azlinda Abu Bakar - Abu Bakar, Azlinda (Faculty of Applied Sciences, 2009)
Presence of heavy metals in the aquatic systems has become a serious problem. As a result, there has been a great deal of attention given to new technologies for removal of heavy metal ions from contaminated waters. Biosorption is one such emerging technology which utilized naturally occurring waste materials to sequester heavy metals from industrial wastewater. The aim of the present study was to utilize the locally available agricultural waste materials for heavy metal removal from industrial wastewater. In this study, the removal of chromium(VI) and lead(II) was done by using bamboo waste. The effects of initial concentration, pH, adsorbent dose, and contact time were studied. The highest percentage removals for chromium and lead were 43% up to 51% and 92% up to 95% respectively. The adsorption of chromium and lead by bamboo waste increased at the higher initial concentration and higher adsorbent doses. Higher chromium adsorption was observed at lower pHs, and maximum chromium removal obtained at pH 2. In contrast, higher lead adsorption was observed at higher pHs, and maximum lead removal obtained at pH 6. The results of this study showed that adsorption of chromium by bamboo waste reached to optimum condition at 45 min. On the other hand, the adsorption of lead has no such significant change but the optimum contact time occurred at 30 min. The obtained results showed that the adsorption of chromium(VI) and lead(II) by bamboo waste follows Freundlich isotherm equation with a correlation coefficient equal to 0.9311 and 0.9398 respectively. The results indicate that bamboo waste can be employed as a low cost adsorbents in the removal of chromium(VI) and lead(II) from industrial wastewater.